STRATEGI PENINGKATAN PEROLEHAN PENDAPATAN BADAN USAHA MILIK DAERAH (STUDI KASUS : PERUSAHAAN DAERAH AIR MINUM KABUPATEN SEMARANG TAHUN 2008 – 2013) - Nindya Prillianti; Dzunuwanus Ghulam Manar; Turtiantoro . (Journal of Politic and Government Studies, 2014)
As a Local Government Company, PDAM Semarang Regency has an important role in supporting local revenue (PAD). In 2008-2011 the company was not able to meet its target of government local revenue due to management unhealthy. However, in 2012 the company was able to show as one of the business entities that succed to contribute to local government revenue. The issues that examined in this study is about factors that change of PDAM Semarang Regency during 2008 - 2013, efforts and incentives that being made to increase revenue and the role of local government in stimulating the enterprises improvement. This study used a qualitative research approach with case study research. This study has problems limitations that developmental of PDAM Semarang Regency in 2008 to 2013 that directly affect to company's revenue.Based on the obtained results the study indicates that improvement of PDAM Semarang Regency were influenced by various factors from both internal and external factors , such as leadership, demands of tariff adjustments, demands of improvement employee welfare, demands of society and demands of contribution to local local. Efforts that have been made by the company to increase revenue were improving quality of human resources, customer service improvement, reduction of NRW (Non-Revenue Water),increasing of SR (House Connection), and network management. While theincentives itself also comes from internal and external corporation, debtrestructuring was one of them. Semarang Regency Government also plays animportant role in development of PDAM by forming a regulatory agency,establishing regulation support of Equity Investments and supporting of tariffadjustment policy.PDAM requires to continue and to optimize its performance inimplementing service delivery to local revenue. Therefore PDAM SemarangRegency should continue to expand network and increase promoting for houseconnection (SR) so that the company's revenue would be increaseKeywords : local revenue, Local Government Company (BUMD), PDAM